Black hole jets, accretion discs and dark energy - Potter, WJ (2013)
Black hole jets and accretion discs are the most extreme objects in modern astrophysics whilst dark energy is undoubtedly the most mysterious. This thesis focuses on understanding these three topics. The majority of this thesis is dedicated to investigating the structure and properties of black hole jets by modelling their emission. I develop an inhomogeneous jet model with a magnetically dominated parabolic accelerating base, transitioning to a slowly decelerating conical jet, with a geometry set by radio observations of M87. This model is able to reproduce the simultaneous multiwavelength spectra of all 38 Fermi blazars with redshifts in unprecendented detail across all wavelengths. I constrain the synchrotron bright region of the jet to occur outside the BLR and dusty torus for FSRQs using the optically thick to thin synchrotron break. At these large distances their inverse-Compton emission originates from scattering CMB photons. I find an approximately linear relation between the jet power and the transition region radius where the jet first comes into equipartition, transitions from parabolic to conical and stops accelerating. The decreasing magnetic field strength and increasing bulk Lorentz factor with jet power are the physical reasons behind the blazar sequence. I calculate the conditions for instability in a thin accretion disc with an α parameter which depends on the magnetic Prandtl number, as suggested by MHD simulations. The global behaviour of the instability induces cyclic flaring in the inner regions of the disc, for parameters appropriate for X-ray binary systems, thereby offering a potential solution to a long standing problem. Finally, I calculate the effect of an interacting quintessence model of dark energy on cosmological observables. I find that a scalar-tensor type interaction in the dark sector results in an observable increase in the matter power spectrum and integrated Sachs-Wolfe effect at horizon scales.